2002
DOI: 10.1093/jac/49.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa cells adapted to benzalkonium chloride show resistance to other membrane-active agents but not to clinically relevant antibiotics

Abstract: Our objective was to determine whether strains of Pseudomonas aeruginosa can adapt to growth in increasing concentrations of the disinfectant benzalkonium chloride (BKC), and whether co-resistance to clinically relevant antimicrobial agents occurs. Attempts were made to determine what phenotypic alterations accompanied resistance and whether these explained the mechanism of resistance. Strains were serially passaged in increasing concentrations of BKC in static nutrient broth cultures. Serotyping and genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 24 publications
6
84
2
2
Order By: Relevance
“…Biocide resistance in bacteria is known to involve several mechanisms (Loughlin et al 2002;Abdel Malek et al 2002, 2009Russell 2003) thus when a small increase in MIC is observed it indicates the possible disabling of one biocide target (Gilbert and MacBain 2001). Cross-resistance to BIT on the other hand, showed significant (p < 0.05) three-fold increase in the MIC from 32 to 85 g/mL (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biocide resistance in bacteria is known to involve several mechanisms (Loughlin et al 2002;Abdel Malek et al 2002, 2009Russell 2003) thus when a small increase in MIC is observed it indicates the possible disabling of one biocide target (Gilbert and MacBain 2001). Cross-resistance to BIT on the other hand, showed significant (p < 0.05) three-fold increase in the MIC from 32 to 85 g/mL (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for increased resistance to PE is the physiological adaptation of the envelope to prevent entry of the biocide. Changes in susceptibility towards biocides have been correlated with OM changes (Loughlin et al 2002;Abdel Malek et al 2002;Winder et al 2000;Brozel and Cloete 1994). It is known that a major mechanism of resistance to biocides is reduced uptake due to impermeability or efflux (Russell 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, other authors [26] reported that organisms isolated from any given niche, medical, environmental, or industrial, have different mechanisms of adhesion and retention, mainly due to changes in their structural components, such as pili, �mbriae, and adhesive surface proteins that have adapted differently over time through selective pressures. Furthermore, exposure to antimicrobials may as well induce changes in cell surface hydrophobicity and surface charge that can alter bacterial adhesion properties [27].…”
Section: Discussionmentioning
confidence: 99%